A study on strategies of Sarawak Consolidated Industries Berhad (SCIB) to achieve competitive advantages in industrialised building system (IBS) industries in Kuching / Abu Bakar Ahmat and Rosalina Suai - Ahmat, Abu Bakar; Suai, Rosalina (2014)
Industrialised Building System (IBS) is defined as a products, systems and techniques used in making less labour-oriented, faster as well as quality controlled. This article aims examine the current strategy and propose future strategy of Sarawak Consolidated Industries Berhad (SCIB) competitive advantage in Industrialised Building System (IBS) industries in Kuching. As one of the main manufacturers of the IBS in Sarawak, it is vital for SCIB to recognize their competitive advantages in order to become a market leader in the IBS industry in Kuching and indirectly being the business entity that in line with Government aspiration to build houses within Sarawak through the IBS technology. We provide recommendation which focus on proposed on future strategies for SCIB pertaining to competitive advantage for further improvement.